« Une vie partagée ». Entretien avec Stéphane Breton - Stéphane Breton (Centre d´Histoire et Théorie des Arts, 2021)
In this discussion, Stéphane Breton takes an interest in the ethical and aesthetic dimensions that documentary films imply, more particularly in the framework of the ethnographic field. The film-maker gives prominence to the ethnocentric angle of the notion of precariousness that may ensue from too general an approach, blind therefore to human dignity. Thus, Stéphane Breton invites to make a distinction between precariousness and destitution, precariousness and frugality. The discussion enters precisely into the ethnographer’s work trying to delimit – through a literary, philosophical scope as well as a cinema one – the place of the film-maker, the rules he builds up. While looking for instants of apparition, this cinema of the period in between has no fear to film wait in order to reveal, to extract from the sensible world, the « lyricism of the ordinary », including in very dark situations.